1988
DOI: 10.4315/0362-028x-51.12.935
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Microorganisms in a Pork Processing Establishment

Abstract: Airborne microorganisms were enumerated in the various processing rooms of a commercial pork slaughter and further processing plant, every other month for a year. The room where sausage emulsions were prepared had higher airborne aerobic bacteria and yeast-mold counts than the other rooms sampled. The mean log aerobic bacteria counts per 0.028 m3 across months were 1.83, 1.83, 1.82, 1.71, 1.93, 2.48, 2.08, 1.62, and 0.95 for the evisceration, offal, carcass cooler, carcass breaking, curing cellar, sausage emul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…Previous research has shown that airborne or aerosolized microbes in commercial processing facilities are found in higher concentrations than those reported in the present study. Microbes were found to be present at 2.0 to 2.3 log 10 cfu/100 L of air in slaughter houses (Rahkio and Korkeala 1997), 0.3 to 2.5 log 10 cfu/0.028 m 3 in a pork slaughter and further processing plant (Kotula and Emswiler-Rose 1988), and 1.8 to 3.0 cfu/100 L in a dairy processing plant (Ren and Frank 1991). We hypothesize that if the console filtration units are able to reduce airborne microbes (down to a background level) when concentrations are very low, they should be effective at reducing airborne contamination at higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that airborne or aerosolized microbes in commercial processing facilities are found in higher concentrations than those reported in the present study. Microbes were found to be present at 2.0 to 2.3 log 10 cfu/100 L of air in slaughter houses (Rahkio and Korkeala 1997), 0.3 to 2.5 log 10 cfu/0.028 m 3 in a pork slaughter and further processing plant (Kotula and Emswiler-Rose 1988), and 1.8 to 3.0 cfu/100 L in a dairy processing plant (Ren and Frank 1991). We hypothesize that if the console filtration units are able to reduce airborne microbes (down to a background level) when concentrations are very low, they should be effective at reducing airborne contamination at higher concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Emphasis should be placed on air quality because of the possibility of contamination of food products with pathogenic and spoilage organisms. There has been considerable research conducted on the incidence of airborne contamination in meat processing plants and how to monitor microbial levels in the air (Knudston and Hartman 1993;Kotula and Emswiler-Rose 1988). However, little research has been done to reduce the incidence of airborne contamination in meat processing plants.…”
Section: Introductionmentioning
confidence: 99%
“…Lenhart et al (1982) found total concentrations of airborne bacteria between 3.6 · 10 5 and 6.5 · 10 5 CFU/m 3 at the 'moving rail' location (ACFM). Kotula and Kinner (1964) found total concentrations of airborne bacteria between 3.1 · 10 4 and 1.1 · 10 5 at the 'moving rail' location and 8.1 · 10 3 CFU/m 3 in the area of the separation of innards (ACFM).…”
Section: Discussionmentioning
confidence: 99%
“…There are two possible sources of food contamination: direct, or primary source, consisting in naturally polluted raw materials (e.g., meat from infected animals), and secondary source, defined as "cross-contamination," consisting in transport/transfer of microorganisms from human or animal feces, mucous membranes, hair, infected wounds, dirt and dust, working environment and tools, air, etc. Among the secondary sources of food contamination, air undoubtedly plays a key role (Kang and Frank 1990;Kotula and Emswiler-Rose 1988;Lutring et al 1997). In fact, although airborne microorganisms are natural contaminants of indoor environments, an increase in their load could represent a risk factor, especially for the potential contamination of foods with undesirable spoiling and pathogenic bacteria (Di Giulio et al 2010).…”
Section: Introductionmentioning
confidence: 99%